Etika Bisnis Dalam Penanganan Data Pasien: Tanggung Jawab Rumah Sakit Gigi Dan Mulut Iik Bhakti Wiyata Kediri di Era Big Data - Bramanto, R. Handi; Sikki, Nurhaeni; Rahmawati, Feti; Khaneisya, Rashell Puteri; Wulandari, Apriliana Ayu (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to explore business ethics in handling patient data at the IIK Bhakti Wiyata Dental Hospital in Kediri, especially in the context of the big data era. With the increasing use of information technology in the health sector, ethical challenges related to patient data privacy and security are becoming increasingly complex. The research method used is a qualitative approach, with data collection through in-depth interviews, observations, and document analysis. The results of the study indicate that the hospital has developed clear policies and procedures to protect patient data, including aspects of privacy protection and staff responsibilities. The implementation of good business ethics has been shown to have a positive impact on the quality of health services, with higher levels of patient satisfaction and increased trust in the institution. However, this study also identified several gaps, including the need for further research on the implementation of business ethics in the context of new technologies and the challenges faced in maintaining data confidentiality in the digital era.